Enhanced Thermoelectric Properties of Pb‐doped BiCuSeO Ceramics. (30th July 2013) - Lan, Jin‐Le; Liu, Yao‐Chun; Zhan, Bin; Lin, Yuan‐Hua; Zhang, Boping; Yuan, Xun; Zhang, Wenqing; Xu, Wei; Nan, C.‐W.
<x xml:space="preserve">Abstract</x> A high‐performance thermoelectric oxyselenide BiCuSeO ceramic with ZT > 1.1 at 823 K and higher average ZT value (ZTave ≈0.8) is obtained. The heavy doping element and nanostructures can effectively tune its electronic structure, hole concentration, and thermal conductivity, resulting in substantially enhanced mobility, power factor, and thus ZT value. This work provides a path to high‐performance thermoelectric ceramics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>